Brain and Human Body Modeling 2020 2020
DOI: 10.1007/978-3-030-45623-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Robustness in Neural Circuits

Abstract: Complex systems are found everywherefrom scheduling to traffic, food to climate, economics to ecology, the brain, and the universe. Complex systems typically have many elements, many modes of interconnectedness of those elements, and often exhibit sensitivity to initial conditions. Complex systems by their nature are generally unpredictable and can be highly unstable. However, most highly connected complex systems are actually quite stable and resistant to disruption from minor changes in parameters [1]. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The ResNet50 network model parameters were obtained through the migration study less, high precision, deep residual layer network structure is complex, which solves the problem of low efficiency based on large training data sets and makes training more precise. Calculating the specificity, sensitivity, accuracy, and AUC revealed that the training model was highly robust (27), which provided external verification, with values of 100.00, 70.70, 86.90, and 98.39%, respectively. Finally, the features extracted from the training images were visualized by a heat map displaying the lung and the region near the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The ResNet50 network model parameters were obtained through the migration study less, high precision, deep residual layer network structure is complex, which solves the problem of low efficiency based on large training data sets and makes training more precise. Calculating the specificity, sensitivity, accuracy, and AUC revealed that the training model was highly robust (27), which provided external verification, with values of 100.00, 70.70, 86.90, and 98.39%, respectively. Finally, the features extracted from the training images were visualized by a heat map displaying the lung and the region near the heart.…”
Section: Discussionmentioning
confidence: 99%